Bu-Shen-Huo-Xue Decoction Ameliorates Diabetic Nephropathy by Inhibiting Rac1/PAK1/p38MAPK Signaling Pathway in High-Fat Diet/Streptozotocin-Induced Diabetic Mice - Wang, Weisong; Long, Hongping; Huang, Wei; Zhang, Ting; Xie, Lihua; Chen, Cheng; Liu, Jianhe; Xiong, Dan; Hu, Wei (Frontiers in Pharmacology, 2020)
Diabetic nephropathy (DN), a leading cause of end-stage renal disease, is associated with high morbidity and mortality rates worldwide and the development of new drugs to treat DN is urgently required. Bu-Shen-Huo-Xue (BSHX) decoction is a traditional Chinese herbal formula, made according to traditional Chinese medicine (TCM) theory, and has been used clinically to treat DN. In the present study, we established a high-fat diet (HFD)/streptozotocin (STZ)-induced diabetic mouse model and treated the mice with BSHX decoction to verify its therapeutic effects in vivo. Ultraperformance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was applied to analyze the chemical composition and active compounds of BSHX decoction. Markers of podocyte epithelial-mesenchymal transition (EMT) and the Rac1/PAK1/p38MAPK signaling pathway were evaluated to investigate the mechanism underlying function of BSHX decoction. BSHX decoction effectively alleviated diabetic symptoms, according to analysis of the renal function indicators, serum creatinine, blood urea nitrogen, serum uric acid, and urinary albumin excretion rate, as well as renal histopathology and ultrastructural pathology of DN mice. We identified 67 compounds, including 20 likely active compounds, in BSHX decoction. The podocyte markers, nephrin and podocin, were down-regulated, while the mesenchymal markers, α-SMA and FSP-1, were up-regulated in DN mouse kidney; however, the changes in these markers were reversed on treatment with BSHX decoction. GTP-Rac1 was markedly overexpressed in DN mice and its levels were significantly decreased in response to BSHX decoction. Similarly, levels of p-PAK1 and p-p38MAPK which indicate Rac1 activation, were reduced on treatment with BSHX decoction. Together, our data demonstrated that BSHX decoction ameliorates renal function and podocyte EMT via inhibiting Rac1/PAK1/p38MAPK signaling pathway in HFD/STZ-induced diabetic mice. Further, we generated a quality control standard and numerous potential active compounds from BSHX decoction for DN.